Pain Management and Shared Decision-Making in Office-Based Gynecologic Procedures: Evidence-Based Strategies and Clinical Perspectives - Aymane Ouriaghli; Ayadine Abdeladim; Alilou Ismail; Moukit Mounir; Rahmoune Mohammed; Moulay El Mehdi El Hassani; Kouach Jaouad; Baba Habib Moulay Abdellah (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Pain during office-based gynecologic procedures is a frequent source of patient distress and may negatively affect satisfaction, adherence to care, and willingness to undergo future procedures. Optimizing pain management and integrating shared decision-making are therefore essential components of high-quality gynecologic practice.Evidence Acquisition: A narrative, non-systematic review of the literature was conducted using PubMed/MEDLINE, Scopus, Web of Science, and the Directory of Open Access Journals (DOAJ). Articles published between 2005 and 2025 were identified using keywords related to gynecologic procedures, pain management, analgesia, and shared decision-making. Randomized controlled trials, meta-analyses, observational studies, guidelines, and selected French-language publications were included. Evidence was qualitatively assessed based on methodological quality and clinical relevance.Results: Pain is commonly reported during office gynecologic procedures in the absence of targeted interventions. Systemic analgesics alone appear to provide limited intra-procedural pain relief, whereas local anesthetic techniques and procedural modifications are associated with reduced pain. Vaginoscopic hysteroscopy, small-diameter instruments, and saline distension media have been associated with improved tolerance. Shared decision-making has been associated with lower perceived pain, reduced anxiety, and higher patient satisfaction across procedures.Conclusions: Effective pain management in office gynecology requires a multimodal, patient-centered approach. Combining evidence-based analgesic strategies with procedural optimization and shared decision-making may improve patient experience and procedural acceptance.Keywords: Office gynecologic procedures; Pain management; Intrauterine device; Endometrial biopsy; Hysteroscopy; Shared decision-making